On a small collection of mysids (Crustacea, Peracarida, Mysida) from the southern Gulf of California, western Mexico, with the description of new species of Mysidium and Cubanomysis - Hendrickx, Michel E.; Hernández-Payán, José Carlos; Gómez-Gutierrez, Jaime (Zootaxa, 2023)
Four species of Mysida were collected in the southwestern Gulf of California, Mexico, including a new species of Mysidium (Mysidium), Metamysidopsis frankfiersi, Siriella gracilis, and a new species of Cubanomysis. The new species of Mysidium is the eleventh species in this genus, with species represented along both coasts of the Americas. It is the third species occurring in the eastern Pacific. The new species of Cubanomysis is the third species in this genus; the other two occur in California and in the western Atlantic.